2010 Information Security for South Africa 2010
DOI: 10.1109/issa.2010.5588281
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Forensic Readiness framework for South African SME's

Abstract: In this digital age, most business is conducted electronically. This contemporary paradigm creates openings for potentially harmful unanticipated information security incidents of both a criminal or civil nature, with the potential to cause considerable direct and indirect damage to smaller businesses. Electronic evidence is fundamental to the successful handling of such incidents. If an organisation does not prepare proactively for such incidents it is highly likely that important relevant digital evidence wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 3 publications
0
16
0
1
Order By: Relevance
“…As a result, researchers have suggested that organisations implement well-defined policies to support forensic readiness [8], [20]. Barske, et al [20] assert that these policies include how systems are monitored, under what conditions data is preserved, data retention times, as well as policies on how investigations are to be undertaken. Rowlingson [8] adds that policies should also cover topics such as identifying data sources, determining data collection and secure data storage.…”
Section: Analysis Of Forensic Readiness Approachesmentioning
confidence: 99%
“…As a result, researchers have suggested that organisations implement well-defined policies to support forensic readiness [8], [20]. Barske, et al [20] assert that these policies include how systems are monitored, under what conditions data is preserved, data retention times, as well as policies on how investigations are to be undertaken. Rowlingson [8] adds that policies should also cover topics such as identifying data sources, determining data collection and secure data storage.…”
Section: Analysis Of Forensic Readiness Approachesmentioning
confidence: 99%
“…Barske et al. also add that although the need for digital forensics and digital evidence in organizations has been explored (as has been the need for digital forensic readiness within organizations), decision makers still need to understand what is needed within their organizations to ensure digital forensic readiness.…”
Section: The Proposed Taxonomy Of Challenges For Digital Forensicsmentioning
confidence: 99%
“…Digital forensic readiness looks for proactively collecting digital evidence and preparing the infrastructure of the organization in question for reactive digital forensic investigation [39]. As a result, both collecting evidence and preparing infrastructure of the organization for forensics investigation has to be addressed by the digital forensic readiness policy.…”
Section: Policymentioning
confidence: 99%